Atherosclerosis and Osteoporosis. Common Targets for the Effects of Cardiovascular and Anti-Osteoporotic Drugs (Part II). The Effect of Antiosteoporotic Drugs on the Vascular Wall State - I. A. Skripnikova; O. V. Kosmatova; M. A. Kolchinа; M. A. Myagkova; N. A. Alikhanova (Столичная издательская компания, 2019)
In the second part of the literature review, data are presented on the possible effect of anti-osteoporosis therapy on the vascular wall and the development of calcification. The discovery of common biological substances involved in the development of atherosclerosis, calcification of the vascular wall and osteoporosis attracts the attention of scientists in terms of targets for assessing the effects of already known drugs or developing new drugs that can simultaneously prevent or slow the progression of both atherosclerosis and osteoporosis. Currently, various groups of drugs for the treatment of osteoporosis have been studied to prevent or reduce the progression of subclinical atherosclerosis and calcification. Both antiresorptive drugs (bisphosphonates, monoclonal antibodies to RANKL, selective estrogen receptor modulators), and bone-anabolic therapy, which includes teriparatide, were studied. However, there are a few such studies and the most promising drugs that have a preventive effect in the early stages of atherosclerotic damage are bisphosphonates. Other classes of antiosteoporotic drugs did not reveal a positive effect on the vascular wall, and some of them increased the cardiovascular risk. Divergences in the results of experimental and clinical studies attract attention. If in the experiment almost all drugs for the treatment of osteoporosis had an atheroprotective effect and suppressed vascular calcification, then in clinical conditions only bisphosphonates confirmed the positive effect on the vascular wall.